2021
DOI: 10.1002/jcpy.1242
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Sensory Imagery for Consumer Psychology

Abstract: This review of mental imagery research has the core objective of fostering more research on the topic of sensory imagery. The review is organized around a conceptual framework highlighting (a) how mental imagery is formed, (b) the elicitation and elaboration of mental imagery, (c) the multi‐modal nature of sensory imagery, and (d) the consumer behavior consequences of mental imagery. This conceptual framework provides many new lenses through which researchers can view prior findings, and thereby motivates inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 157 publications
(299 reference statements)
0
27
0
1
Order By: Relevance
“…Elder and Krishna (2021) noted that sensory impression is related to an individual’s perception of the intensity of stimuli. How is intensity achieved in a sensory-driven experience?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Elder and Krishna (2021) noted that sensory impression is related to an individual’s perception of the intensity of stimuli. How is intensity achieved in a sensory-driven experience?…”
Section: Resultsmentioning
confidence: 99%
“…(Xu, Marketing Manager) However, informants' (managers and customers) views on what SBE represents have also extended our understanding of SBE where perception of the phenomenon is described in terms of overall affects and feeling states, rather than the stimulation from individual sensory cues. This is how one customer respondent commented: Elder and Krishna (2021) noted that sensory impression is related to an individual's perception of the intensity of stimuli. How is intensity achieved in a sensory-driven experience?…”
Section: Sensory Brand Experiencementioning
confidence: 93%
See 2 more Smart Citations
“…For example, Schlosser (2003) showed that when consumers interact with a product online (vs. passively view it), they engaged in greater mental imagery and had increased cognitive elaboration. Even if consumers do not have access to all of the sensory stimuli that are desirable for their decision-making, mental simulation can nevertheless still facilitate multisensory perceptual re-enactments ( Petit et al, 2019 ; Elder and Krishna, 2021 ). For example, the visual exposure to appetising pictures of food not only activates regions of the visual cortex that represent object shape, it also activates gustatory areas in order to produce conceptual inferences about taste ( Simmons et al, 2005 ).…”
Section: The Challenge Of Consumer Consciousness In Xrmentioning
confidence: 99%